Investigating the influence of iron–carbon microelectrolysis on the performance and microbial community of constructed wetlands. (17th November 2019) - Wei, Fang; Zhou, Qingwei; Wu, Weihong; Bian, Zhengfu; Feng, Xiaoyi; Li, Jinye; Shi, Mingjuan
Abstract: Iron–carbon microelectrolysis (Fe–C ‐ME) has been used extensively for the treatment of domestic sewage. In this study, CWs incorporated with Fe–C ‐ME were established, and the performance and microbial community structure of CWs were investigated. The results indicated that CWs incorporated with Fe–C‐ME had better performance for treating domestic sewage. The NO3 ‐ –N, TN and TP removal efficiencies of CWs incorporated with Fe–C‐ME were 82.3, 80.3 and 98.2%, respectively, which were 7.8, 4.7 and 25.2% higher than those of the CWs without Fe–C‐ME. High‐throughput sequencing analysis demonstrated that Fe–C‐ME changed the microbial community structure. For example, some dominant groups at the class level, such as Betaproteobacteria (15.2%), Gammaproteobacteria (10.6%) and Deltaproteobacteria (10.0%), were promoted by Fe–C‐ME. The results demonstrated that the relative abundance of bacteria involved in nitrification, denitrification, polyphosphate accumulation or COD reduction at the genus level thrived because of the presence of Fe–C‐ME, which can improve the performance of CWs.